Rezervisane, grupne, diferencirajuće i suprotne osobine likova u Andrićevoj Prokletoj avliji - Šolak, Zdravko (Slavistična revija, 2010)
This paper presents an analysis of the qualities Ivo Andrić attributes to the characters in his novel The Dammed Yard. In his method, certain rules may be singled out. The given rules are interpreted in this paper using several models. It appears that proposed models are appropriate for fiving a good description of the author's method by which he introduces a large number of characters in quite a short novel, achieving what critics have called "character pluralism".
Keywords: Andrić, Ivo, 1892-1975; Andrić, Ivo: Prokleta avlija; bosanska književnost; literarne študije; literarni liki; novel; roman